PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP KOGNITIF MATA PELAJARAN PENDIDIKAN AGAMA DAN BUDI PEKERTI - Siti Aisah Syafaatin; Dedi romli Triputra; Didik Tri Setiyoko (Universitas Yudharta Pasuruan, 2023)
The purpose of this study is to evaluate the impact of the make-a-match learning paradigm on grade IV cognitive learning outcomes. With a pretest-posttest design, the methodology utilized in this study is a real experimental quantitative approach. Class IV students from SD Negeri 01 Kaliwadas made up the study's population, which consisted of 43 kids, and its sample, which included 24 and 19 students from IV A and IV B, respectively. The experimental class and the control class are the two groups that make up this research's structure. Multiple-choice questions are utilized in the cognitive domain of the instruments used to gather data on cognitive learning outcomes. The PABP learning materials for the apostles of Allah were the source of the study's material. The results indicated that both learning models exhibited an increase in scores between pretest and posttest, implying that there was no difference, however based on the average acquisition of the experimental class, it performed better than the control class